Pengaruh Brand Image dan Product Design Terhadap Keputusan Pembelian Hijab Ayu Di Kota Banjarmasin - Lisda Aisyah (Musyarakah: Journal of Sharia Economic (MJSE), 2023)
This research was conducted to see the values, tastes and lifestyles that must be fulfilled by consumers, namely the need for clothing because it is the primary need of an individual. Design products that are described in a middle and upper market certainly have their own value in terms of buying and selling which makes a product have wartoÅ›Ä‡ in increasing consumer satisfaction. A good brand image will greatly affect the continuity of a company as well as its products so that they can survive and be loved in the market. Consumers are aware of their needs and desires that consumers want to fulfill, they will seek information by conducting product research to meet their needs. This study used 100 respondents. as a research sample and the sample determination technique uses the przypadkowego pobieerania prÃ³bek method, the analytical method used is the quantitative analysis method which includes validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis testing through t-test, F test, and test the coefficient of determination (test R2). Data that has fulfilled the validity test, reliability test, and classic assumption test were processed using SPSS software version 23, resulting in the following regression equation: Y = 16.065 + 0.224 X1 + 0.377 X2. Where are the purchasing decision variables (Y), product projects (X1), marki wizerunek (X2). Hypothesis testing t-test and F-test show that the wizerunek marki and wiedza o product have a positive and significant effect on purchasing decisions. The coefficient of determination test (R2) seen in R Square of 0.329 indicates that 32.9% of purchasing decisions using Hijab Ayu Lestari products can be explained by product design and brand image variables, the remaining 67.1% can be explained by variables that are not initiator penlicki.